THE NEED TO STUDY DEFINITIONS OF SPATIAL CONCEPTS AND SOME METHODOLOGICAL APPROACHES TO LEARNING - Sarukhanyan, A. (SUSh Scientific Proceedings, 2025)
The current state standard of general education clearly defines the goals of the Mathematics in the context of education. One of these goals was considered to promote the development of students' intellectual abilities with mathematical concepts, the formation of their thinking on this basis, the clear formulation of thoughts and the execution of competent judgments, as well as quick orientation in various situations. The development of any scientific field also represents the introduction of a certain system of concepts considered in it. New concepts are also constantly being introduced into the school mathematics course. This fact is reflected in a certain way in the form of requirements both in the state standard of general education and in the standard for the subject ―Mathematics‖, in the subject exemplary programs in the subjects ―Mathematics‖, ―Algebra‖, ―Algebra and Elements of Mathematical Analysis‖, ―Geometry‖. The result of studying concepts should be the core of not only individual concepts, but also the system of concepts of each topic and subject ―Mathematics‖ as a whole. This is facilitated by identifying links between concepts through definition and classification. In the new state standard of general education, a red line is the requirement to acquire skills in introducing, defining, recognizing and applying concepts, but there is still no developed effective methodology for teaching the definition of spatial-metric concepts that would facilitate the full assimilation of definitions of spatial-metric concepts. This article presents not only an effective method of teaching the definition of spatial-metric concepts, but also provides typical spatial-metric examples and tasks with the appropriate methodology, which to a certain extent will fill the gap existing in school textbooks and contribute to the assimilation of spatial-metric concepts